Toward an understanding of the ontology of bliss in the context of modernity - Mukerji, Bithika (My University, 1981)
The thesis begins with the question of modernity and its implications for the Western world. An attempt is made to show that modernity pertains to the mechanised West, rather than to India which, as yet, is only trying to imitate the progress-oriented culture of the West believing that she can be technisized with no loss to her tradition of Vedanta philosophy which speaks only in terms of Freedom as Self-realization. Contemporary orientation in India in re-interpreting the Vedanta philosophy in the light of the demands of 'modernity' are studied in some detail with a view to establishing the thesis that the crucial teachings of the tradition have been glossed over, with the result that a discontinuity with it must be accepted together with the process of Westernization. To demonstrate this alienation, an interpretative analysis of a major text is given which brings out the fact that the trans-natural concerns of the tradition, is integral to it, and any philosophical understanding which makes it irrelevant to the issue of our way of being in the world, falls far short of contemplating the heart of the matter.
Keywords: Religion; Religion